2020
DOI: 10.47104/ebnrojs3.v2i4.168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of The Health Belief Model-Based Education on Preventive Behaviors of Breast Cancer

Abstract: Context: Breast cancer is the main type of cancer affecting women and the fourth most common cancer mortality cause. Approximately one out of eight women worldwide develop breast cancer. Screening prevention plays a vital role in the early detection of breast cancer and reducing mortality rates. Aim: The study aimed to evaluate the effect of the health belief model-based education on breast cancer preventive behaviors. Methods: Quasi-experimental (pre/post-test) design was used in this study. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This finding was in accordance withMahmoud et al, (2020) who proved that there was a positive statistically significant correlation between the studied women's total knowledge (pre and post model implementation), practices (post model implementation), and their total health belief. And, Mousavi et alIran and demonstrated that there was a positive relationship between health knowledge and health-promoting behaviors (HBM).…”
supporting
confidence: 91%
“…This finding was in accordance withMahmoud et al, (2020) who proved that there was a positive statistically significant correlation between the studied women's total knowledge (pre and post model implementation), practices (post model implementation), and their total health belief. And, Mousavi et alIran and demonstrated that there was a positive relationship between health knowledge and health-promoting behaviors (HBM).…”
supporting
confidence: 91%
“…Accordingly, appropriate educational programs should be provided at the national level to institutionalize screening behaviors among women by improving their perception and raising their awareness of breast cancer. Nurses can play a vital role in raising breast cancer awareness among women by organizing comprehensive screening programs 46 .…”
Section: Discussionmentioning
confidence: 99%